INFLUENCE OF SIMULTANEOUSLY INJECTION OF EMBRYONIC CELLS OF LIVER AND BRAIN ON SEVERITY OF ALCOHOL INDUCED HEPATIC INJURY - Petrenko, A.Yu.; Sandomirskiy, B.P.; Yakimova, T.P.; Kovalyov, G.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Influence of simultaneously injection of cells of embryonic liver (CEL) and cells of embryonic brain (CEB) on severity of alcohol induced hepatic injury in rats was studied. It is shown that the intravenous injection of CEL and CEB leads to the improvement the structures of liver at a cellular and tissue level, stimulation of proliferation and regeneration of hepatocytes, normalization of blood flow, activating of the system of mononuclear phagocytes.